Mlake – a hotspot of butterfly diversity in Slovenia - Rudi Verovnik; Marko Kosmač; Peter Valič (Natura Sloveniae)
The Mlake military area in Vipava Valley has been recognized as possibly the most prominent ‘hot spot’ of butterfly diversity in Slovenia. An area of less than one square kilometre hosts 102 butterfly species or almost 57% of the total species confirmed for Slovenia. Among these, 23 species have been recognized as nationally or continentally threatened. Due to recent urbanization, the total area suitable for butterflies has been reduced to less than half, however, the effects on butterfly diversity of the area are not yet visible. The loss of several habitat specialist butterfly species and declines visible from transect monitoring in the last five years do, however, indicate the ongoing process of habitat degradation in Mlake military area. A focused management of the remaining habitats will be required to reverse this process.